Mesenchymal stem cells induce dynamic immunomodulation of airway and systemic immune cells in vivo but do not improve survival for mice with H1N1 virus-induced acute lung injury - Tan, Yuan; Wang, Yan; Souza-Moreira, Luciana; Wang, Chi; Murray, Aidan B. P.; Salkhordeh, Mahmoud; Florian, Maria; McIntyre, Lauralyn; Stewart, Duncan J.; Mei, Shirley H. J. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Influenza A virus (IAV) induced acute lung injury (ALI) is characterized by pronounced proinflammatory activation and respiratory lung dysfunction. In this study, we performed deep immune profiling on airway and circulating immune cells to examine the effect of immunomodulation and therapeutic outcomes of mesenchymal stem cells (MSCs) therapy in mice with IAV-induced ALI. Methods: Animals were inoculated intranasally with H1N1 IAV, followed by intravenous administration of vehicle, or human clinical-grade, bone marrow derived MSCs 24-hour later, and monitored for six days to evaluate the survival. In another set of animals, bronchoalveolar lavage (BAL) fluid and whole blood were collected three days after infection for flow or mass cytometry (CyTOF) immune profiling analysis. Results: Immune cell population and phenotypic shifts in blood were mapped by CyTOF. Increases were observed in granulocytes and myeloid-derived cells in blood from vehicle-treated animals. While MSCs treatment accentuated changes in these populations, naïve B, antibody-secreting B cells and T cells were decreased in MSCs-treated animals at day 3. Compared to sham animals, IAV infection induced a significant 5.5-fold increase BAL total cell counts, including CD4+ and CD8+ T cells, CD19+ B cells, CD11b+Ly6G+ neutrophils, and CD11b+Ly6C+ monocytes. MSCs treatment significantly decreased BAL total cell counts in IAV-infected mice, specifically the number of infiltrating CD4+ T cells and CD11b+Ly6G+ neutrophils. In contrast, there were increases in CD8+ T cells, B cells, and monocytes in the alveolar space in MSCs-treated animals. Phenotypic immune cell profiling of blood and BAL revealed a significantly higher proportion of the monocyte population with the M2 phenotype (CD206) in MSCs-treated animals; however, this failed to confer protective effects in the survival of infected mice or reduce viral titre in the lung. Further investigation revealed that MSCs were susceptible to IAV infection, leading to increased cell death and potentially affecting their efficacy. Conclusion: These findings provided in vivo evidence that MSCs promote the selective recruitment of immune cells to the site of infection during IAV infection, with reductions in proinflammatory phenotypes. However, MSCs offered no survival benefit in IAV-infected animals, possibly due to MSCs’ H1N1 IAV susceptibility and subsequent cell death.